Aspek Teknologi Dalam Jaringan Kerja Sama Perpustakaan dan Informasi Perpustakaan Digital di Kota Medan - Aina Sabriyanti,; Dinda Rizky Anggurini; Rahmat Al-Rasyid; Yusniah Yusniah (Da'watuna: Journal of Communication and Islamic Broadcasting, 2023)
The development of digital library services must begin with the development of human resources in the library. This needs to be done because at this time the field of Information and Communication Technology has become a basic need for libraries. The researcher uses an approach approach with the aim of revealing the data that is decomposed by data sources and participants to find out how the technological aspects in the library cooperation network and digital library information in the city of Medan, to obtain quality results from the research conducted. The results of this study indicate that the collaboration between libraries in the city of Medan is quite good and cooperates with each other, this is marked by the collaboration carried out in the scope of technology and digital library development. Keywords: Information Technology, Cooperation, Library